RESEARCH OF THE PROBLEM OF CHILDREN WITH SPEECH DISORDERS IN PRIMARY CLASS STUDENTS BY FOREIGN SCIENTISTS - Mirzahmatov Bahodir Bahromboy ugli (Galaxy International Interdisciplinary Research Journal, 2022)
The article talks about the research of foreign scientists on the problem of children with speech disorders in elementary school students.